Comparative Analysis of Salt Responsive MicroRNAs in Two Sweetpotato [Ipomoea batatas (L.) Lam.] Cultivars With Different Salt Stress Resistance - Yang, Zhengmei; Dong, Tingting; Dai, Xibin; Wei, Yiliang; Fang, Yujie; Zhang, Lei; Zhu, Mingku; Nawaz, Ghazala; Cao, Qinghe; Xu, Tao (Frontiers in Plant Science, 2022)
Sweetpotato [Ipomoea batatas (L.) Lam.] is an important food, vegetable and economic crop, but its productivity is remarkably affected by soil salinity. MiRNAs are a class of endogenous non-coding small RNAs that play an important role in plant resistance to salt stress. However, the function of miRNAs still remains largely unknown in sweetpotato under salt stress. Previously, we identified salt-responsive miRNAs in one salt-sensitive sweetpotato cultivar “Xushu 32.” In this study, we identified miRNAs in another salt-tolerant cultivar “Xushu 22” by high-throughput deep sequencing and compared the salt-responsive miRNAs between these two cultivars with different salt sensitivity. We identified 687 miRNAs in “Xushu 22,” including 514 known miRNAs and 173 novel miRNAs. Among the 759 miRNAs from the two cultivars, 72 and 109 miRNAs were specifically expressed in “Xushu 32” and “Xushu 22,” respectively, and 578 miRNAs were co-expressed. The comparison of “Xushu 32” and “Xushu 22” genotypes showed a total of 235 miRNAs with obvious differential expression and 177 salt-responsive miRNAs that were obviously differently expressed between “Xushu 32” and “Xushu 22” under salt stress. The target genes of the miRNAs were predicted and identified using the Target Finder tool and degradome sequencing. The results showed that most of the targets were transcription factors and proteins related to metabolism and stress response. Gene Ontology analysis revealed that these target genes are involved in key pathways related to salt stress response and secondary redox metabolism. The comparative analysis of salt-responsive miRNAs in sweetpotato cultivars with different salt sensitivity is helpful for understanding the regulatory pattern of miRNA in different sweetpotato genotypes and improving the agronomic traits of sweetpotato by miRNA manipulation in the future.